2011
DOI: 10.1111/j.1346-8138.2011.01279.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte and monocyte adsorption apheresis for generalized pustular psoriasis

Abstract: Granulocyte and monocyte adsorption apheresis (GCAP) is an extracorporeal circulation therapy that removes activated granulocytes and monocytes. GCAP was initially approved for the treatment of ulcerative colitis, which is attributed to activated granulocytes and macrophages that infiltrate the target tissues. Generalized pustular psoriasis (GPP) is also supposed to be caused by activated neutrophils. In this study, we treated two patients with refractory GPP by using GCAP. Patient 1, a 68-year-old woman who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Among 15 cases, adverse events were reported in three patients, but none were serious, suggesting the safety of GMA . In addition, no serious side‐effects were reported in the case series …”
Section: Chapter V: Strength Of Recommendations and Comments For Eachmentioning
confidence: 74%
See 1 more Smart Citation
“…Among 15 cases, adverse events were reported in three patients, but none were serious, suggesting the safety of GMA . In addition, no serious side‐effects were reported in the case series …”
Section: Chapter V: Strength Of Recommendations and Comments For Eachmentioning
confidence: 74%
“…Comments: The efficacy and safety of GMA in GPP have been shown only in case reports, case series including a report on neutrophilic skin disorders and reviews. [162][163][164][165][166][167] No RCT have been performed, but one multicenter study 32 has shown improvement in the area of erythema, erythema with pustules, and edema, and in the severity score defined in the 2010 guidelines for the management and treatment of GPP. Among 15 cases, adverse events were reported in three patients, but none were serious, suggesting the safety of GMA.…”
Section: Cq18 Is Gma Effective For Gpp?mentioning
confidence: 99%
“…Psoriasis is characterized by increased dermal infiltration of inflammatory cells, neutrophils, macrophages, dendritic cells and natural killer cells . Moreover, infiltration of macrophages, especially around the epidermal–dermal junction, increases in psoriatic skin . Therefore, infiltration of macrophages in the flaky skin mice was examined, and we found that the number of infiltrating macrophages was decreased in the skin of delphinidin‐treated mice, as shown by F4/80 staining, compared with the skin of control mice.…”
Section: Resultsmentioning
confidence: 85%
“…48,49 Moreover, infiltration of macrophages, especially around the epidermal-dermal junction, increases in psoriatic skin. 48,50 Therefore, infiltration of macrophages in the flaky skin mice was examined, and we found that the number of infiltrating macrophages was decreased in the skin of delphinidin-treated mice, as shown by F4/80 staining, compared with the skin of control mice. In addition, delphinidin treatment also reduced Gr-1-positive infiltratory neutrophils in the skin (Fig.…”
Section: Delphinidin Treatment Inhibits Infiltration Of Inflammatory mentioning
confidence: 94%
“…Granulocyte and monocyte adsorption apheresis was first shown to have remarkable effects in patients with ulcerative colitis (4–6), a type of inflammatory bowel disease, which is also commonly characterized by infiltration of the affected tissues by neutrophils. Earlier studies have also shown the efficacy of GCAP in various skin diseases and related disorders, such as pyoderma gangrenosum, psoriatic arthritis, adult Still's disease, Behcet's disease, leg ulcers in rheumatoid arthritis, cutaneous allergic vasculitis and pustular psoriasis, which appear to be attributable to activated neutrophils (7). Histopathologically, GPP is characterized by neutrophilic infiltration of the epidermis that causes Kogoj's spongiotic pustules.…”
Section: Discussionmentioning
confidence: 99%